Shear strength of reinforced and prestressed concrete deep beams - Lu, Hai Yun. (2009)
The studies in this thesis mainly focus on the general behaviour, analysis and design in the shear strength of large reinforced and post-tensioned concrete deep beams. The influence of main steel ratio p, concrete strength fc', shear span-to-overall-height ratio a/h (or shear span-to-effective-depth ratio a/d), overall height h and prestress force on deep beams are investigated.